The perception towards recreational activity participation among foreign students in University Putra Malaysia, Serdang - Mohammad, Nurul Fatihah (2016)
People nowadays are seen already aware about the benefit of pursuing recreational activity during their leisure time. However, the foreign students do not participate in recreational activity and have some constraints that hinders them from taking part in the recreational activity. This study was done to investigate the perception and constraint towards recreational activity participation among foreign students in Universiti Putra Malaysia (UPM). The data were collected using a questionnaire that was being distributed among foreign students in UPM. One hundred and fifty respondents were selected as the sample for this study. All the information obtained from the questionnaire has been analyzed using SPSS. The results of the study indicated that the perception of respondents towards recreational activity is an activity that can reduce stress and as a hobby. However, most of the foreign students do not participate in recreational activities in their life. The main reasons for not participating in recreational activity are the lack of time due to study obligations.